2018
DOI: 10.1002/ange.201803092
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of the Metal Pyrites FeS2, CoS2, and NiS2

Abstract: Atomic layer deposition (ALD) of the pyrite-type metal disulfides FeS 2 ,C oS 2 ,a nd NiS 2 is reported for the first time.T he deposition processes use iron, cobalt, and nickel amidinate compounds as the corresponding metal precursors and the H 2 Splasma as the sulfur source.All the processes are demonstrated to followideal self-limiting ALD growth behavior to produce fairly pure,s mooth, well-crystallized, stoichiometric pyrite FeS 2 ,CoS 2 ,and NiS 2 films.Bythese processes,the FeS 2 ,C oS 2 ,a nd NiS 2 fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…Platinum-based cathode catalysts are most efficient for the HER because of their high electroactivity and remarkable current density in acidic and alkaline solutions. However, the high cost and rare abundance of noble metals hamper their practical application in the industrial scale. Until now, various alternatives, such as dichalcogenides of transition metals (WS 2 , MoS 2 , MoSe 2 , WSe 2 ), pyrites of transition metals (FeS 2 , CoSe 2 ), metal organic frameworks (MOFs), , phosphides of transition metals (CoP, FeP), and carbonaceous materials (carbon nanofibers with Fe–N4, porous carbon with Ni–N x , and many other porous carbon nanosheets) have been demonstrated as efficient catalysts for the HER in acid and alkaline media. However, the catalytic efficiency and durability still remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum-based cathode catalysts are most efficient for the HER because of their high electroactivity and remarkable current density in acidic and alkaline solutions. However, the high cost and rare abundance of noble metals hamper their practical application in the industrial scale. Until now, various alternatives, such as dichalcogenides of transition metals (WS 2 , MoS 2 , MoSe 2 , WSe 2 ), pyrites of transition metals (FeS 2 , CoSe 2 ), metal organic frameworks (MOFs), , phosphides of transition metals (CoP, FeP), and carbonaceous materials (carbon nanofibers with Fe–N4, porous carbon with Ni–N x , and many other porous carbon nanosheets) have been demonstrated as efficient catalysts for the HER in acid and alkaline media. However, the catalytic efficiency and durability still remain unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic layer deposition (ALD) is one of the effective methods to deposit highquality thin films by self-limiting growth mechanism. [19][20][21] ALD is a saturated selflimiting surface chemistry achieving layer-by-layer growth of target films. It is also capable of producing highly uniform films on a large scale through precise atomic control of film composition and thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al reported a universal ALD process to deposit pyrite-type metal disulfides (FeS 2 , CoS 2 , and NiS 2 ). [11] The well-crystallized films prepared with optimized ALD recipes could be uniformly deposited even into deep, narrow trenches with high aspect ratios.…”
mentioning
confidence: 99%